Climate Adaptation Santiago - Krellenberg, Kerstin; Hansjürgens, Bernd (Springer Berlin Heidelberg : Imprint: Springer, 2014)
Th is book addresses the complexity of urbanization, impacts of climate change andclimate change adaptation for the Metropolitan Region of Santiago de Chile, with aspecial focus on the most pressing issues of natural hazards, water and energy supply. The book exemplifi es an integrative, inter- and transdisciplinary approach (IIT) for thedevelopment of adaptation measures, their evaluation and implementation in a decisionsupport framework at the science-policy interface. It builds on scientific analyses of both social and natural scientists, a participatory process with local stakeholders, and a Regional Learning Network between large agglomerations in Latin America. All this led to the development of a Regional Climate Change Adaptation Plan for Santiago de Chile. Th e book is written for scholars of urban management, climate change, planning, governance and hazard research, as well as practitioners in local, regional and international organizations concerned with climate change, climate change impacts, and adaptation in metropolitan regions. While the regional focus is on Latin America the concepts and lessons learned are applicable and relevant to megacities around the world.